Media multitasking: Performance differences between younger and older adults and the role of working memory - Wannagat, Wienke; Martin, Tamara; Nieding, Gerhild; Rohleder, Nicolas; Becker, Linda (Computers in Human Behavior, 2024)
We examined the effects of media multi- vs. single-tasking on performance in a scenario that resembled the media multitasking requirement of many contemporary office workplaces. Older (n = 117, Mage = 70.99 years, SD = 5.18) and younger adults (n = 109, Mage = 22.86, SD = 3.93) performed a repetitive computer-based reading task (Task 1) that, in the multitasking condition, was repeatedly interrupted by news app messages that the participants had to read for comprehension (Task 2). In the single-tasking condition, the messages appeared after Task 1 was completed. In both conditions, participants afterwards answered questions about the message content. Performance in Task 1 was poorer in the multi- than in the single-tasking condition, but there was no evidence of greater multitasking costs in the older compared to the younger adults. Regarding Task 2, there was no indication of multitasking costs in any age group, but older adults showed poorer comprehension, regardless the task requirements. This effect of age was mediated via working memory updating abilities. Thus, the way information is commonly presented in social media, that is, usually bit-by-bit and not ordered by topic, seems to disadvantage older readers due to poorer updating abilities. All in all, the results provide some indication that, in terms of task accuracy, older adults do not appear to be at a disadvantage compared to younger adults when it comes to coping with the multitasking demands of digitalized societies.
CRIS-Team Scopus Importer:2025-02-04